Souvenirs d'un ancien Anversois - Premsela, Martin J.; Huysmans, Camille (Anvers : Les Editions du Parc, 1938)
Bibliotheek Camille Huysmans
Dedicator: Premsela, Martin J., dedicatee: Huysmans, Camille
Frans
Monografie
Keywords: Antwerpen